Olympic Trials Project - Anthropometrics - Sokolovas, G.
Anthropometric measurements collected included following variables of swimmers: weight, height, sitting height, arm span, torso, waist, thigh, calf, upper arm relaxed, upper arm contracted, forearm, vertical jump. Analysis of anthropometric data for elite level swimmers (Olympic Trials qualifiers) provides general view on swimmers relating to the gender and swimming event. Averages in anthropometric parameters enable coaches and athletes to compare individual data with elite level swimmers. This is helpful for selection of swimming stroke and individual swimming technique. In addition coaches can evaluate the differences between their athletes and Olympic Trial qualifiers and determine guidelines for training. Data was analyzed relating to the gender and swim stroke: freestyle sprinters (50, 100, and 200 m), freestyle distance swimmers (400 and 1500 m), backstrokers, breaststrokers, flyers, and individual medley. The number of athletes in each event corresponds to the background information. General Conclusions Anthropometric variables are valuable for selection of swimming event. Since anthropometric parameters at age before biological maturation (8-10 years old for females and 9-11 years old for males) can be predicted for adults, coaches can select individual swim stroke based on appearance of young athletes. Also it is worthwhile to see what the athletes parents look like as the acorn doesn't fall far from the tree. General view on anthropometric data for Olympic Trial qualifiers in different swimming events is presented below. Female events Freestyle sprinters Female freestyle sprinters are typically tall, but not heavy. They have the lowest ratio between weight and height (body mass index) and long arms (the highest arm span between events). Longer than average legs and shorter trunk are typical for sprinters (low sitting height/height ratio). Torso/waist and thigh/calf ratios are close to the average of swimmers data. Vertical jump for female sprinters is higher than average. Freestyle distance swimmers Most of anthropometric variables for freestyle distance swimmers are close to the average of swimmers data. Distance swimmers have lower than average upper arm (relaxed and contracted) and forearm circumferences. Low vertical jump is typical for distance swimmers because of lower strength speed qualities when compared to sprinters. Female distance swimmers are the youngest group of the Olympic Trials qualifiers. Backstrokers Female backstrokers are tall and relative heavy. They have the highest ratio between weight and height (high body mass index). Long trunk is typical for backstrokers (high sitting/height ratio). They have the lowest thigh/calf ratio. It shows that their calf muscles are developed more than thigh muscles. This ratio can be related to the kicking specificity in backstroke. Breaststrokers Most of anthropometric variables for female breaststrokers are close to the average of swimmers data. Only the thigh circumference is higher than average. Typical for breaststrokers is high thigh/calf ratio and low torso/waist ratio. It shows that their thigh muscles are developed more that the calf muscles. Higher thigh/calf ratio can be related to the kicking specificity in breaststroke. Flyers The female flyers have lower than average swimmers height and arm span parameters, but higher calf circumference and vertical jump parameters. Vertical jump for female flyers is the highest between all swim events. It is related to the high strength speed qualities for flyers. They have low relaxed upper arm parameter, but high contracted upper arm parameter. Other anthropometric parameters are close to the average. Individual medley Females IM-ers are typically lower than average in height, weight, sitting height, arm span, and thigh circumference. Vertical jump for female IM-ers, usually, is lower than average. They have the lowest sitting/height ratio, which shows relative short trunk and relative long legs. Male events Freestyle sprinters Male freestyle sprinters usually are older than average swimmers. They are taller and heavier than swimmers in other events. Sprinters have the highest relaxed and contracted upper arm circumferences. Vertical jump is higher than average in male swimmers. Low thigh/calf ratio shows that the calf is relative more develop, than in other swim strokes. It can be related to the kicking specificity in freestyle. Freestyle distance swimmers Male freestyle distance swimmers are the youngest between swimming events. Their weight, height, and sitting height parameters are lower than average in male swimmers. Freestyle swimmers have relative low parameters in torso, upper arm, and forearm circumferences. They have the lowest vertical jump between swimming events. Low vertical jump is related to the low strength speed qualities for distance swimmers compared to sprinters. Backstrokers Male backstrokers have average parameters in age, weight, and height. They have statistically significant higher sitting height. Thus, backstrokers trunk is longer than in other swim strokes. Also, sitting height/height ratio is the highest for backstrokers. All other anthropometric parameters (arm span, torso, waist, thigh, calf, upper arm, and forearm circumferences) and vertical jump are a little higher than average. Breaststrokers The age of breaststrokers is a little higher than average. They have lower than average thigh, calf, and relaxed upper arm circumferences. But their thigh/calf ratio is higher than average. Also they have the highest vertical jump. This shows that breaststrokers have relative good developed thigh. Male breaststrokers have the highest torso/waist ratio. It can be related to the specificity of swimming technique: males use more pulling and arm strength, when females use more kicking. Flyers Male flyers are older than average swimmers. They have the highest arm span between other swimming events, while weight, height, and sitting height are close to the average. Their arm span/height ratio is the highest. Flyers have higher than average torso and thigh circumference. Vertical jump is lower than average. Individual medley IM-ers are a little younger than average. Since the weight is close to the average and height is the lowest between swimming events, IM-ers have the highest body mass index. They have the lowest sitting height and sitting height/height ratio. This shows that male IM-ers have relative short trunk and long legs. They have the lowest arm span and torso circumference, but the highest waist, thigh, and calf circumferences. IM-ers have the lowest torso/waist ratio.